Development of Antiarrhythmic Therapy-Resistant Ventricular Tachycardia, Ventricular Fibrillation, and Premature Ventricular Contractions in a 15-Year-Old Patient - Yozgat, Can Yilmaz; Yesilbas, Osman; Iscan, Akin; Yurtsever, Ismail; Temur, Hafize Otcu; Bayramova, Nigar; Ergun, Gokce; Tekin, Nur; Yozgat, Yilmaz (Journal of Pediatric Intensive Care, 2020)
Sudden cardiac arrest (SCA) is the sudden cessation of regular cardiac activity so that the victim becomes unresponsive, with no signs of circulation and no normal breathing. Asystole, ventricular tachycardia (VT), ventricular fibrillation (VF), and pulseless electrical activity are the underlying rhythm disturbances in the pediatric age group. If appropriate interventions (cardiopulmonary resuscitation-CPR and/or defibrillation or cardioversion) are not performed rapidly, this condition progresses to sudden death. There have not been many reported cases of the approach and treatment of cardiac arrhythmias after SCA. Herein, we would like to report a case of a 15-year-old female patient with dilated cardiomyopathy (DCM) who was admitted to our clinic a year ago, and while her left ventricular systolic functions were improved, SCA suddenly occurred. Since the SCA event occurred in another city, intravenous treatment of amiodarone was done immediately and was switch to continuous infusion dose of amiodarone until the patient arrived at our institution's pediatric intensive care unit (PICU) 3 hours later. During the patient's 20-day PICU hospitalization, she developed pulseless VT and VF from time to time. The patient's pulseless VT and VF attacks were brought under control by the use of a defibrillator and added antiarrhythmic drugs (amiodarone, flecainide, esmolol, and propafenone). Intriguingly, therapy-resistance bigeminy with premature ventricular contractions (PVCs) continued despite all these treatments. The patient did not have adequate blood pressure measured by invasive arterial blood pressure monitoring while having bigeminy PVCs. The intermittent bigeminy PVCs ameliorated rapidly after intermittent boluses of lidocaine. In the end, multiple antiarrhythmic therapies and intermittent bolus lidocaine doses were enough to bring her cardiac arrhythmias after SCA under control. This case illustrates that malign PVC's should be taken very seriously, since they may predispose to the development of VT or VF. Also, this case highlights the importance of close vigilance of arterial pressure tracings of patients with bigeminy PVCs which develop after SCA and should not be accepted as normal.
Keywords: bigeminy premature ventricular contractions; pediatric intensive care unit; lidocaine; ventricular tachycardia; ventricular fibrillation